AN ACTION RESEARCH ON MANAGING AND DIRECTING DRAMA IN EDUCATIONAL INSTITUTIONS AND BLENDING THE POSTCOLONIAL FEMINIST DRAMA - D, Divya Priya (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper focusses on the difficulties in the production of a live drama in an educational institution from auditioning the actors to seamless performance on stage. The actors were chosen from students of literature doing their undergraduate and postgraduate studies. A postcolonial drama, The Lion and The Jewel by Wole Soyinka was chosen and the drama was staged. The researcher has been the director of the drama and a field study has been studied on the process of creating a successful drama. It involves stage management, producing the play, directing, acting, light design, set design and costume design. Stage management is one of the crucial factors in a drama which needs to be taken care of from the practice sessions to the show time. The outcome of the show relies entirely on the management of the stage. In this study Yoruba’s drama is taken and replicating them was a tougher one which includes costume, realistic stage setting, lighting, sound setting and their dances. The drama is also chosen to highlight the sufferings of women in African society and how they are victimized. All these aspects are previously designed and experimented practically to find out the shortcomings in staging a live drama in an educational institution. Questionnaires are also designed and circulated among the actors for further study.